37ps-Precision Time-Resolving Active Quenching Circuit for High-Performance Single Photon Avalanche Diodes - Giulia Acconcia; Massimo Ghioni; Ivan Rech (IEEE Photonics Journal)
Time-resolved imaging by means of single-photon avalanche diodes (SPADs) has achieved widespread interest in recent years, especially since technological progress has opened the way to the development of multichannel time-correlated single-photon counting (TCSPC) acquisition systems. Unfortunately, currently available TCSPC imagers feature relatively low performance with respect to state-of-the-art single-channel systems. A real breakthrough in this field would be the exploitation of large arrays of high-performance SPAD detectors developed by means of dedicated fabrication processes, usually referred to as custom technology. Custom-technology SPADs require external electronics potentially leading to interconnection issues for densely integrated arrays. In this paper, we present a new fully integrated front-end circuit able to provide both quenching/reset and timing functionalities while requiring a single connection toward the SPAD. This is the first fully integrated circuit reported in literature that can provide both the timing information about the photon time of arrival with a jitter as low as 37 ps and apply high-voltage pulses up to 50 V in order to meet the requirements of several detectors, including the new red-enhanced SPAD. Combining these two capabilities in a single circuit strongly reduces the complexity of the connection between an array of custom-technology SPADs and the relative external front end, thus paving the way for the exploitation of high-performance SPADs in TCSPC imaging systems.